Genome-wide identification and expression analyses of the pectate lyase (PL) gene family in Fragaria vesca - Xiaolong Huang; Guilian Sun; Zongmin Wu; Yu Jiang; Qiaohong Li; Yin Yi; Huiqing Yan (BMC Genomics, 2023)
Abstract Background Pectate lyase (PL, EC 4.2.2.2), as an endo-acting depolymerizing enzyme, cleaves α-1,4-glycosidic linkages in esterified pectin and involves a broad range of cell wall modifications. However, the knowledge concerning the genome-wide analysis of the PL gene family in Fragaria vesca has not been thoroughly elucidated. Results In this study, sixteen PLs members in F. vesca were identified based on a genome-wide investigation. Substantial divergences existed among FvePLs in gene duplication, cis-acting elements, and tissue expression patterns. Four clusters were classified according to phylogenetic analysis. FvePL6, 8 and 13 in cluster II significantly contributed to the significant expansions during evolution by comparing orthologous PL genes from Malus domestica, Solanum lycopersicum, Arabidopsis thaliana, and Fragaria×ananassa. The cis-acting elements implicated in the abscisic acid signaling pathway were abundant in the regions of FvePLs promoters. The RNA-seq data and in situ hybridization revealed that FvePL1, 4, and 7 exhibited maximum expression in fruits at twenty days after pollination, whereas FvePL8 and FvePL13 were preferentially and prominently expressed in mature anthers and pollens. Additionally, the co-expression networks displayed that FvePLs had tight correlations with transcription factors and genes implicated in plant development, abiotic/biotic stresses, ions/Ca2+, and hormones, suggesting the potential roles of FvePLs during strawberry development. Besides, histological observations suggested that FvePL1, 4 and 7 enhanced cell division and expansion of the cortex, thus negatively influencing fruit firmness. Finally, FvePL1-RNAi reduced leaf size, altered petal architectures, disrupted normal pollen development, and rendered partial male sterility. Conclusion These results provide valuable information for characterizing the evolution, expansion, expression patterns and functional analysis, which help to understand the molecular mechanisms of the FvePLs in the development of strawberries.